"Total displacement of curved surface sliders under nonseismic and seismic actions: A parametric study". Issue 12 (11th May 2017) - Quaglini, Virginio; Gandelli, Emanuele; Dubini, Paolo; Limongelli, Maria Pina
Summary: The re‐centring capability is recognized as a fundamental function of any effective isolation system, not only because it is associated to small or negligible deformation at the end of the earthquake but rather because it prevents displacement build up that may limit the capability of the structure to withstand aftershocks and future earthquakes. The current Eurocode recommends to estimate the maximum total displacement of the isolated system as the superposition of the nonseismic offset displacement resulting from permanent actions, long‐term deformations and thermal movements of the structure, and of the amplified seismic displacement induced by the design earthquake. For systems endowed with low re‐centring capability, the estimation shall also account for the possible accrual of displacements during the lifetime of the structure. However, the aforementioned criteria have never been evaluated for curved surface sliders, which are characterized by an inherent nonlinear behaviour. The study aims at giving more insight into the matter by conducting a parametric study based on one‐directional nonlinear response time history analyses and considering a variety of seismic scenarios. The first part of the study investigates the effect of a nonseismic displacement on the earthquake‐induced displacement and formulates a criterion to evaluate the capability of curved surface sliders to provide a seismic response independent of the offset displacement. The response of the isolation system to natural sequences of earthquakes, where the offset displacement is the residual displacement from the previous shake, is addressed in the second part of the paper. The provisions of the Eurocode are eventually checked against the observed data.